Synthesis and optimization of octavalent bolaamphiphile preparation with terminal D-mannose residues - V. B. Gostenin; I. S. Shchelik; Yu. L. Sebyakin (Тонкие химические технологии, 2015)
In this article a scheme was proposed, and the synthesis of octavalent bolaamphiphile with terminal D-mannose residues was carried out. The technique of the laboratory synthesis of this compound was improved using optimisation of the key step of the compound synthesis and purification of the final compound. All intermediate steps of the final compound synthesis were described in detail. The terminal D-mannose residues will allow binding with mannose-specific lectins, for example, on the surface of E. coli morbidising the gastrointestinal tract. The resulting compound can be used as a potential anti-adhesion agent to prevent the development of infectious diseases.